2001
DOI: 10.1046/j.1471-5740.2001.d01-6.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of refrigerator biofilm bacteria for application in the food service environment

Abstract: Refrigerator biofilm formation in food environments can result in spoilage and food safety problems. Biofouling of food contact surfaces are difficult to combat, and while there are significant risks involved with tolerating their presence, methods for their removal are not commonly available. In this study, biofilms were grown on plastic refrigerator trays. Cultures of mixed wild strains were started using kitchen scraps suspended in nutrient broth. Biofilms were allowed to mature with approximately 109 CFU p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Since foodservice workers think that the low temperatures of refrigerators may decrease bacterial populations, refrigerators may not be cleaned periodically. Bacterial contaminations from unwashed raw foods, leaking packages, and hands may increase bacterial populations on internal surfaces of refrigerators (Michaels and others 2001; Jackson and others 2007). A recent study by Jackson and others (2007) found that home refrigerators were contaminated with S .…”
Section: Resultsmentioning
confidence: 99%
“…Since foodservice workers think that the low temperatures of refrigerators may decrease bacterial populations, refrigerators may not be cleaned periodically. Bacterial contaminations from unwashed raw foods, leaking packages, and hands may increase bacterial populations on internal surfaces of refrigerators (Michaels and others 2001; Jackson and others 2007). A recent study by Jackson and others (2007) found that home refrigerators were contaminated with S .…”
Section: Resultsmentioning
confidence: 99%
“…C. sakazakii may be present on raw retail meats; this pathogen has been previously reported in sausages, pork, camel, and poultry meat (19). Bacteria from contaminated raw foods, leaking packages, and hands may be introduced to domestic refrigerators, countertops, and other food preparation areas, posing a risk of indirect contamina tion during subsequent food preparation activities (43). In previous studies, homes have been identified as an important point of cross-contamination through improper handling of raw food products (4,40).…”
Section: Discussionmentioning
confidence: 97%
“…Bacteria from unwashed raw foods, leaking packages, unclean hands, and unclean container surfaces introduced into domestic refrigerators can directly contaminate other stored foods and persist on internal refrigerator surfaces. This in turn creates the risk of indirect long-term contamination during subsequent food preparation (27).…”
mentioning
confidence: 99%